Differential responses of two plant species with different ecological niches to long-term nitrogen and phosphorus addition in temperate meadow steppe - Chen, Li; Zhao, Dan; Yang, Yunrui; Wei, Yi; Wang, Zhihui; Wang, Hongyi (Frontiers in Plant Science, 2025)
IntroductionGlobal nitrogen (N) and phosphorus (P) deposition are fundamentally altering soil nutrient availability and species interactions in grassland ecosystems. However, the long-term interplay between N and P in shaping ecological niche differentiation among co-existing plant species remains poorly understood.MethodsLeveraging a decade-long nutrient addition experiment in a temperate meadow steppe, this study investigated the response strategies of the dominant upper-canopy grass Leymus chinensis and the subdominant lower-canopy forb Potentilla bifurca by analyzing their phenotypic and nutrient traits.ResultsWe found that P. bifurca exhibited greater phenotypic plasticity than L. chinensis, a difference that was amplified under combined NP addition. Notably, the two nutrient regimes drove opposing niche dynamics: N addition alone exacerbated P limitation, reducing phenotypic trait differences between the species (niche distance decreased from 0.12 to 0.07) and leading to niche convergence. In contrast, combined NP addition alleviated P limitation, enhanced the plasticity of P. bifurca, and drove niche separation (distance increased to 0.16). Correlation and random forest analyses revealed that the aboveground biomass of L. chinensis was primarily associated with N-related traits, whereas that of P. bifurca was strongly associated with P-use efficiency traits.ConclusionOur results demonstrate that long-term N and P addition regulate interspecific competition by modulating soil N/P ratio and driving divergent trait responses, thereby shaping the niche partitioning between co-existing species.